Adapting the skills of a future purchaser within the organizations - Toma, Simona (Technium Social Sciences Journal, 2026)
Starting from the contemporary role of the purchaser within a company’s life, this qualitative research examines the competencies currently required and it presents an image of the purchaser profile needed in the near future. The literature review served as a basis for an empirical investigation among local large organizations. The methods used were in-depth bibliographic documentation and semi-structured interviews addressed to sixteen purchasing executives from the local banking organizations and also IT&C. The study focuses on the competencies the buyers will be requested in the near future, considering the challenges encountered.